2006
DOI: 10.1111/j.1742-6723.2006.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure measurements on children in the emergency department

Abstract: The present study demonstrates that BP measurement in the ED is both relatively infrequent and inconsistent. Further research into this area is required to determine the usefulness and feasibility of routine BP measurements in children presenting to the ED. This might improve the quality of health care and positively impact on public health for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…There was a failure to measure and record blood pressure,8 a vital sign in children, particularly in cases of shock and head injury. Guidance from the National Institute for Health and Clinical Excellence advises that all children seen with a head injury should have measured as a minimum several vital signs including blood pressure 9.…”
Section: Discussionmentioning
confidence: 99%
“…There was a failure to measure and record blood pressure,8 a vital sign in children, particularly in cases of shock and head injury. Guidance from the National Institute for Health and Clinical Excellence advises that all children seen with a head injury should have measured as a minimum several vital signs including blood pressure 9.…”
Section: Discussionmentioning
confidence: 99%
“…There are few data on BP follow-up during childhood of these babies, despite evidence that there may be associated hypertension in late childhood [2]. Studies have shown that measurement of blood pressure in infancy is infrequently and inadequately performed [3,4]. Normative blood pressure data in healthy infants using modern oscillometric techniques is also limited.…”
Section: Introductionmentioning
confidence: 93%
“…This guidance reflects a tendency not to measure BP in children in Emergency Departments (EDs) the world over. One Australian study reported only 22% of children attending an ED had BP measured (3). In relation to inpatients, systolic BP is a component of the Bedside Paediatric Early Warning Score (4) but as BP is often neglected in the routine observations performed on hospitalised children, opportunities for early detection of the deteriorating child may be missed.…”
Section: Introductionmentioning
confidence: 99%